Optimal inspection and mission abort policies for systems subject to degradation - Zhao, Xian; Sun, Jinglei; Qiu, Qingan; Chen, Ke (European journal of operational research, 2021)
•Dynamic condition based mission abort policies for systems subject to degradation are developed.•The structural properties of the optimal abort policies are investigated.•The detailed comparison between the optimal policy and several heuristic policies are conducted.•Mission reliability and system survivability are derived under the proposed heuristic policies. Safety-critical systems are commonly required to perform missions in various engineering fields. Failures of safety-critical systems may result in irretrievable economic losses and significant damages. To enhance the system survivability, mission abort is usually conducted if the failure risk becomes too high. This paper investigates the joint optimization of inspection and condition based mission abort policies for systems subject to continuous degradation. Dynamic mission abort decisions are considered based on the degradation level together with the time in mission. The problem is formulated within the framework of Markov decision process to minimize the expected costs of inspection, mission failure and system failure. In addition to deriving some structural properties, we also numerically evaluate several heuristic policies where mission reliability and system survivability are derived. Numerical studies are presented to validate the obtained results.